2019
DOI: 10.1371/journal.ppat.1008169
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the unfolded protein response for replication by porcine reproductive and respiratory syndrome virus

Abstract: The unfolded protein response (UPR) in the endoplasmic reticulum (ER) constitutes a critical component of host innate immunity against microbial infections. In this report, we show that porcine reproductive and respiratory syndrome virus (PRRSV) utilizes the UPR machinery for its own benefit. We provide evidence that the virus targets the UPR central regulator GRP78 for proteasomal degradation via a mechanism that requires viral glycoprotein GP2a, while both IRE1-XBP1s and PERK-eIF2α-ATF4 signaling branches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 82 publications
(84 reference statements)
2
32
0
Order By: Relevance
“…2C). To measure total PRRSV RNA, a pair of internal primers in the viral open reading frame 7 (ORF7) gene were used to amplify all subgenomic mRNA and genomic RNA by quantitative real-time PCR (RT-qPCR) (32,33). Axl knockdown did not significantly influence the abundance of PRRSV RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C). To measure total PRRSV RNA, a pair of internal primers in the viral open reading frame 7 (ORF7) gene were used to amplify all subgenomic mRNA and genomic RNA by quantitative real-time PCR (RT-qPCR) (32,33). Axl knockdown did not significantly influence the abundance of PRRSV RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus (PRRSV, also known as beta-arterivirus suid 1) infects pigs and inflicts a great economic strain on the farming industry, but frequent antigenic variations have hampered the development of a vaccine [102][103][104][105]. PRRSV primarily infects alveolar macrophages where it inhibits PKR to enable its own replication [102].…”
Section: Other Respiratory Virusesmentioning
confidence: 99%
“…Interestingly, UPR signalling by PERK and IRE1α appears to be more important than PKR in promoting stress granule formation during PRRSV infection [104,105], but PERK may also play a role in severe pneumonias caused by co-infection with PRRSV and bacteria, since the resulting eIF2α phosphorylation inhibits IFN and tumour necrosis factor (TNF) production. Curiously, ISR activation during PRRSV infection might increase viral titres [103]. ATF4 is held in the cytosol by the viral proteins nsp2 and nsp3, preventing its migration to the nucleus.…”
Section: Other Respiratory Virusesmentioning
confidence: 99%
“…The spliced (XBP1s) and unsliced (XBP1u) forms were analyzed by digesting the RT-PCR products with the restriction enzyme Pst I (FD0615) (Thermo Fisher Scientific, Hampton, NH, USA). Followed by purification of digested PCR products with 1.5% agarose gel electrophoresis and analysis by using the gel imaging system (Federal bioproducts Inc., Manufacturer, UK) [28,42,43].…”
Section: Xbp1 Mrna Splicing Assaymentioning
confidence: 99%
“…Studies have shown that the interaction of dengue virus envelope protein with GRP78, calreticulin, and calnexin promote proper folding and assembly of viral proteins for replication [ 27 ]. The UPR induced by porcine reproductive and respiratory syndrome virus (PRRSV) suppresses viral replication and RNA synthesis [ 28 ]. PERK and IRE1, but not the ATF6 pathway, can be activated by HCMV lytic replication [ 29 ].…”
Section: Introductionmentioning
confidence: 99%